Detection of Leishmania spp. using parasitological, serological and molecular assays in asymptomatic and sick cats from an endemic area of visceral leishmaniosis in Brazil - Alves-Martin, Maria Fernanda [UNESP]; Paixão, Mirian dos Santos [UNESP]; da Silva, Diogo Tiago; Tenório, Michely da Silva [UNESP]; Alves, Maria Luana; Starke-Buzetti, Wilma Aparecida [UNESP]; Pereira, Virginia Bodelão Richini; Lucheis, Simone Baldini [UNESP] (Asian Pacific Journal of Tropical Medicine Press, 2017)
Objective: To analyze the prevalence of feline leishmaniosis in 55 asymptomatic cats or assess clinical disease in a visceral leishmaniasis-endemic area using parasitological, serological and molecular techniques. Methods: Fifty-five adult domestic and non-purebred cats held at an animal shelter in a rural area of the municipality of Ilha Solteira, São Paulo, Brazil, a region endemic for canine visceral leishmaniosis, were evaluated. A total of 5 mL of blood was collected from each animal, for blood culture, serological (indirect fluorescent antibody test, soluble extract ELISA, ELISA recombinant K39 antigen) and molecular tests (PCR). At the time of blood collection, the cats underwent clinical evaluation for the presence of clinical signs. Results: Flagellate protozoa were found in nine blood cultures (16.4%). Seropositivity by indirect fluorescent antibody test was observed in 32 serum samples (62.7%). ELISA-SE showed seropositivity in 37 cats (72.5%), while ELISA-rK39 revealed positive results in 11 cats (21.6%). Leishmania spp. was detected by PCR in whole blood samples from five cats (9.1%). Based on clinical evaluation, it was possible to detect the presence of clinical signs (alopecia, emaciation, pinna lesions, nose lesions, skin lesions) in 30 animals (54.5%). Conclusions: To the knowledge of the authors, this is the first report of Leishmania spp. in domestic cats in the epidemiological cycle of leishmaniosis in the studied area, requiring more attention in the establishment of preventive steps to control this disease.
Keywords: Brazil; Clinical signs; Diagnostics; Domestic cat; Visceral leishmaniosis